Kualitas Pelayanan Petugas Pemadam Kebakaran Dalam Penanggulangan Bencana Kebakaran pada Dinas Pemadam Kebakaran Kota Makassar - Sahid H, M.; Syukur, Alam Tauhid; Kamariah, Najmi; Prianggoro, Bimo Adi (Universitas Negeri Surabaya, 2023)
The implementation of fire fighting performance at the Makassar City Fire Department is considered not optimal in carrying out its duties as a public service provider. There are still complaints from the public about the service quality of the Makassar City Fire Department. Based on these problems, this study aims to examine and analyze the service quality of firefighters at the Makassar City Fire Department. In this study, to determine the service quality of firefighters, it was analyzed using five aspects, namely tangibles, reliability, responsiveness, assurance, and empathy. Meanwhile, the method used is descriptive method with a qualitative approach and data collection techniques using interviews, observation, and document review. The results of the study indicate that from the analysis of five aspects above, as well as with the increasingly complex development in the Makassar City area, it takes speed and alertness from firefighters to always be responsive and alert to all information related to fire disasters. In addition, community participation is also required to be active and able to synergize with officers in carrying out fire fighting duties, so that officers do not experience difficulties in carrying out their duties in the field. It is recommended that the government, in this case the Makassar City Fire Department, provide education to the public about the synergy of performance as well as strengthen the competence and infrastructure of officers so that they can be optimal in carrying out their duties in the field related to handling fire disasters.